2000
DOI: 10.1073/pnas.97.24.13063
|View full text |Cite
|
Sign up to set email alerts
|

A role for ubiquitin ligase recruitment in retrovirus release

Abstract: Retroviral Gag polyproteins have specific regions, commonly referred to as late assembly (L) domains, which are required for the efficient separation of assembled virions from the host cell. The L domain of HIV-1 is in the C-terminal p6 gag domain and contains an essential P(T͞S)AP core motif that is widely conserved among lentiviruses. In contrast, the L domains of oncoretroviruses such as Rous sarcoma virus (RSV) have a more N-terminal location and a PPxY core motif. In the present study, we used chimeric Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
297
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 287 publications
(319 citation statements)
references
References 40 publications
18
297
1
3
Order By: Relevance
“…A link between the formation of exosomes and HIV budding in macrophages is supported by recent evidence showing viral budding into intracellular compartments containing MHC II and CD63 and by the presence of these two MVE-associated proteins at high levels on the resulting virion particles within the MVE (16). Previous studies have also shown a requirement for proteins critical to the formation of exosomes in MVEs, such as Tsg-101 (26) and ubiquitin (27), for HIV budding. To date, exosomes from T-cells, Epstein-Barr virus-transformed B-cells, erythrocytes, and dendritic cells have been analyzed (21), but exosomes from primary macrophages have not been studied.…”
supporting
confidence: 49%
“…A link between the formation of exosomes and HIV budding in macrophages is supported by recent evidence showing viral budding into intracellular compartments containing MHC II and CD63 and by the presence of these two MVE-associated proteins at high levels on the resulting virion particles within the MVE (16). Previous studies have also shown a requirement for proteins critical to the formation of exosomes in MVEs, such as Tsg-101 (26) and ubiquitin (27), for HIV budding. To date, exosomes from T-cells, Epstein-Barr virus-transformed B-cells, erythrocytes, and dendritic cells have been analyzed (21), but exosomes from primary macrophages have not been studied.…”
supporting
confidence: 49%
“…Although one cannot rule out the possibility that K63-linked polyubiquitination might affect these processes indirectly, these data, together with analysis of PRLr degradation in the presence of specific proteasomal inhibitors, raise serious doubts regarding a major role of proteasomes (which usually require K48-linked chains) (10) in the proteolytic fate of PRLr. Interpretation of previously reported effects of proteasome inhibitors on the degradation of either PRLr (29) or erythropoietin/growth hormone receptors (42,45) should include consideration of the possibility of an indirect effect of these inhibitors on the lysosomal pathway, which could be suppressed via depletion of the ubiquitin pool (37). Interestingly, we have never observed a ligandstimulated formation of a PRLr fragment either when following the fate of endogenous PRLr in T47D or 293T cells or when studying recombinant N-terminally HA-tagged or C-terminally Flag-tagged proteins.…”
Section: Discussionmentioning
confidence: 99%
“…1A) in Ste2p-Ub3xR were mutated individually or in clusters of 2-4 residues, and yeast strains expressing the mutant chimeras were assayed for their ability to internalize the Ste2p ligand, ␣-factor. Met 1 was not mutated; neither was Ser 28 , since this residue is an alanine in human ubiquitin. All of the receptor-mutant ubiquitin chimeras specifically bound a similar amount of ␣-factor at the cell surface, indicating that the chimeric proteins were transported to the plasma membrane.…”
Section: Functions Of Ubiquitin Surface Domains In Yeastmentioning
confidence: 99%